Fabricating Ba0.5Cs0.5Fe2As2 films on BaFe2As2 substrates and their superconducting properties. (1st September 2022) - Wang, Chunlei; Chen, Wangyang; Tang, Qingbin; Li, Yigang; He, Tian; Chen, Dong; Lei, Qiankun; Chen, Rui; Hou, Siyu; Tu, Youchao; Yu, Benhai
Abstract: Ba0.5 Cs0.5 Fe2 As2 films on BaFe2 As2 substrates with T c ∼ 29.8 K have been synthesized by a simple one-step self-flux method. Quasi-single-crystal Ba0.5 Cs0.5 Fe2 As2 films are more favorable in 122-type crystal structure but not in 1144-type. Based on the obtained Ba0.5 Cs0.5 Fe2 As2 films, the temperature and angle-dependent resistivity are measured under a magnetic field up to 9.0 T. The results indicate that the films exhibited high upper critical fields, strong flux pinning potential and low anisotropic factors. By scaling the resistivity within the framework of the anisotropic Ginzburg–Landau (GL) theory, the angle-dependent resistivity of Ba0.5 Cs0.5 Fe2 As2 films under various magnetic fields at a fixed temperature can be scaled to one curve. Both the Werthamer–Helfand–Hohenberg and GL methods give a similar anisotropic factor ∼3.0. Ba0.5 Cs0.5 Fe2 As2, cannot naturally grow bulk single crystals but only form film on the surface of BaFe2 As2 crystal under normal pressure. It is reasonable to infer that surface strain should play a key role in the formation of Ba0.5 Cs0.5 Fe2 As2 films. Thus, it is believed that element doping or substitution may be one of the most effective methods to obtain doped-Ba0.5 Cs0.5 Fe2 As2 bulk single crystals.